2021
DOI: 10.1177/0036850421998175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin C in critically ill patients with sepsis and septic shock: A meta-analysis

Abstract: The objective of this study was to investigate the efficacy of vitamin C in patients experiencing sepsis and septic shock. The PubMed, Embase and Cochrane Library databases were searched for randomized controlled trials (RCTs) about vitamin C treatments for critically ill patients suffering from sepsis and septic shock from inception until December 31, 2019. The primary outcome was mortality, and the secondary outcomes were the ICU length of stay and the dose of vasopressors. A meta-analysis of nine RCTs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, the ICU length of stay did not differ between the two groups. Therefore, multicenter and randomized controlled trials are needed to further clarify the safety and effectiveness of using vitamin C to treat patients with sepsis and septic shock [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ICU length of stay did not differ between the two groups. Therefore, multicenter and randomized controlled trials are needed to further clarify the safety and effectiveness of using vitamin C to treat patients with sepsis and septic shock [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…117,118 Neither found a significant difference in the primary endpoint of mortality (28-day mortality, or long-term mortality). Of three published meta-analyses limited to RCTs, [119][120][121] two showed a reduction in 72-hour SOFA scores among patients in the intervention groups, but no difference in mortality. 119,120 One, which was limited to RCTs of vitamin C infusion only, shows a significant reduction in 28-day mortality (odds ratio: 0.60, with 95% CI: 0.42-0.85).…”
Section: Clinical Studies Of Vitamin C In Sepsismentioning
confidence: 96%
“…Multiple systematic reviews with meta-analyses evaluating vitamin C in the critically ill and in sepsis have been published. 3,56,[114][115][116][117][118][119][120][121][122] Two of the five meta-analyses of vitamin C in sepsis and/or septic shock included all study types (i.e., RCTs, before/after, cohort studies), and included studies of vitamin C alone or in combination with thiamine and/or hydrocortisone. 117,118 Neither found a significant difference in the primary endpoint of mortality (28-day mortality, or long-term mortality).…”
Section: Clinical Studies Of Vitamin C In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled data using a random effect model showed a 19% reduction in odds for hospital mortality, while among the 15 RCTs, this effect could not be observed. Feng et al [30] included nine RCTs with a 584 septic patients and revealed no significant differences between the vitamin C and control group on the primary endpoint 28-day mortality or secondary endpoints including vasopressor dose and length of stay. Lastly, the SRMA by Xing et al [35], including 18 RCTs with N = 2001 critically ill patients, reported reduced ICU and hospital length of stay without significant effects on the longest follow-up mortality, hospital or ICU mortality and change in SOFA scores.…”
Section: Metaanalysesmentioning
confidence: 99%